EFFECT OF PERSONAL PROTECTIVE EQUIPMENT (PPE) ON WORKER PRODUCTIVITY IN CV ALDEAZ SEJAHTERA PRINTING IN DEPOK - Fajar Ramadhan (Kreator, 2020)
Personal protective equipment is an important part of the safety and health ofworkers in the company. Personal protective equipment (PPE) is one of the factors that can affect the productivity of workers and comes with various types of personal protective equipment such as eye, head, ear, respiratory, hand, foot and body protection. Personal protective equipment can affect down time and can prevent or reduce the level of work accidents that result in lost time incidents that lead to decreased production and cause losses to employees and the company. Work accidents can be reduced by implementing the 5 Rs and requiring the use of personal protective equipment. By implementing the use of company personal protective equipment it can increase the safety and welfare of workers and can alsoincrease the productivity of these workers.Keywords: PPE, OHS and Printing Industry